High‐throughput and automation advances for accelerating single‐cell cloning, monoclonality and early phase clone screening steps in mammalian cell line development for biologics production. (20th September 2021) - Tejwani, Vijay; Chaudhari, Minal; Rai, Toyaj; Sharfstein, Susan T.
Abstract: Mammalian cell line development is a multistep process wherein timelines for developing clonal cells to be used as manufacturing cell lines for biologics production can commonly extend to 9 months when no automation or modern molecular technologies are involved in the workflow. Steps in the cell line development workflow involving single‐cell cloning, monoclonality assurance, productivity and stability screening are labor, time and resource intensive when performed manually. Introduction of automation and miniaturization in these steps has reduced the required manual labor, shortened timelines from months to weeks, and decreased the resources needed to develop manufacturing cell lines. This review summarizes the advances, benefits, comparisons and shortcomings of different automation platforms available in the market for rapid isolation of desired clonal cell lines for biologics production.